A Note on Weakly Generalized Closed Sets in Topological Spaces - K. Karuppiah (Mathematical Statistician and Engineering Applications, 2023)
The objective of this paper is to extend the concept of a new class of weakly generalized closed sets called weakly r-closed sets by applying generalized closed sets. I introduce the definition of weakly r-closed sets in topological spaces and study the relationships of such sets.